Tracheal Structure of the Moraceae Family and Its Contribution to High School Biology Learning - Derbi Lestari; Ermayanti Ermayanti; Didi Jaya Santri (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
This study investigates the tracheal structure of several selected Moraceae species and its potential as a medium for learning high school biology. The method used is descriptive and maceration technique, with the aim of describing in detail the structure of tracheal cells in several species of plants of the Moraceae family. The research was conducted at the Biology Education Laboratory of Sriwijaya University. The samples used were jackfruit (Artocarpus heterophyllus), breadfruit (Artocarpus altilis), mulberry (Morus nigra), banyan (Ficus benjamina) and banyan beringin (Ficus callophylla) stems. Parameters observed included trachea type, secondary wall thickening type, perforation type, and length and diameter of tracheal cells. The results showed that the types of tracheal found were reticulate, spiral, and anular. Secondary wall thickening types are reticulate I, reticulate II, Spiral I, Spiral II, and Ring. The types of perforations found were scalariform and simple. The length of tracheal cells varied from 247.16 µm to 832.34 µm, with the longest tracheal element found in the trachea of Artocarpus heterophyllus and the shortest in the trachea of Ficus benjamina. Meanwhile, the diameter of the tracheal elements ranged from 11.06 µm to 127.69 µm, with the widest diameter in the trachea of Artocarpus altilis and the narrowest in the trachea of Ficus benjamina. in addition, based on the validation results, the booklet developed from this study scored 91.66%, which is categorized as very valid. This indicates that the booklet is suitable for use and has the potential to be a learning resource to support biology learning.